2007
DOI: 10.1007/s00268-007-9018-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of intestinal malrotation in adults

Abstract: Intestinal malrotation is a rare but important cause of abdominal pain in adults. It may present with chronic or acute symptoms. Laparotomy and laparoscopy are alternative and feasible techniques with low rates of complications for the treatment of intestinal malrotation in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 32 publications
0
85
0
Order By: Relevance
“…Recurrent symptoms in such cases are usually considered to be due to adhesions and one may be inclined to adopt a non-operative approach. Fu et al [16] reported only two recurrences in a series of 12 adults treated for symptomatic malrotation with one of them requiring a reoperation and the other managed conservatively. It is believed that the increasing use of CT scan will enable one to make such diagnosis with certainty preoperatively as this has the overall advantage of detecting the abnormal location of the midgut as well as any other intraabdominal anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent symptoms in such cases are usually considered to be due to adhesions and one may be inclined to adopt a non-operative approach. Fu et al [16] reported only two recurrences in a series of 12 adults treated for symptomatic malrotation with one of them requiring a reoperation and the other managed conservatively. It is believed that the increasing use of CT scan will enable one to make such diagnosis with certainty preoperatively as this has the overall advantage of detecting the abnormal location of the midgut as well as any other intraabdominal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent volvulus as a cause of bowel obstruction following Ladd's operation for midgut malrotation is very rare both in children and adult life and very few of such cases have been reported in literature [15][16][17][18][19][20][21] (Table 1). Recurrent symptoms in such cases are usually considered to be due to adhesions and one may be inclined to adopt a non-operative approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its white cell count Counterclockwise detorsion of the bowel, division of the coloduodenal band and division of adhesions around the superior mesenteric artery to broaden the base of the mesentery were performed. (13) Importantly, there were no lymphatic malformations, enlarged lymph nodes or retroperitoneal tumours at the root of the mesentery and retroperitoneum, which might have obstructed the lymphatic flow. Hence, the cause of the chylous ascites could be confidently attributed to intestinal malrotation, which resulted in temporary lymphatic obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…All patients diagnosed to have malrotation need to be operated as the surgery is associated with least morbidity and the consequences of not intervening may be life threatening [18]. However, this is a point of debate.…”
mentioning
confidence: 99%